The effect of subjective perception of cognition on emotional functioning in adults with long-term neurological and neuropsychiatric disorders. Issue 22 (22nd October 2020) - Mitrushina, Maura; Tomaszewski, Robert
Abstract: Purpose: To examine effects of subjective perception and objective status of cognition on emotional functioning in a sample of adults with long-term neurological and neuropsychiatric disorders. Method: N = 65. Subjective measures were derived from the self-ratings on the Problem Checklist (PCL) from the HI-FI; the objective status was represented by combined externally standardised scores on neuropsychological tests across three cognitive domains: verbal memory, executive functioning, and psychomotor speed. Results: No relationship was found between self-ratings of cognitive competence and performance on neuropsychological tests. Based on the results of the multiple regression analysis, approximately 40% of the variability in emotional functioning was explained by self-perceived cognitive and physical competence, while the addition of objective measures of cognition increased predictive capacity by only 1.3%. The awareness scores were calculated as the difference between objective performance scores and self-ratings of cognition. Overall, the sample demonstrated a tendency towards low awareness of cognitive deficits. Patients who overestimated cognitive deficits self-rated emotional functioning at a significantly lower level, while those with average or low awareness of deficits were equally emotionally content. Conclusions: Self-perception of competence, rather than objective level of functioning influence emotional well-being and quality of life in individuals with long-term disabilities in our study. IMPLICATIONS FOR REHABILITATION: Cognitive deficits are common consequences of neurological dysfunction. This study shows that self-perception of cognitive competence, rather than objective level of cognitive functioning has critical influence on emotional well-being and perceived quality of life. An addition of psychotherapeutic intervention directed at alleviation of self-perception bias is likely to improve emotional well-being and enhance efficiency of rehabilitation efforts in patients with long-term disabilities due to neurological disorders. Based on our findings, patients with long-term disabilities could benefit from psychotherapy to improve their self-perception and quality of life.